Collaborative Governance for Stunting Reduction: A Qualitative Case Study from Bangka Regency, Indonesia - Then Suyanti; Dedeh Maryani; Petrus Polyando (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Stunting remains a major public health challenge in Indonesia, requiring integrated and multisectoral responses. Collaborative governance provides a framework for aligning stakeholder roles in local-level health interventions. This study examines the implementation of collaborative governance in stunting mitigation efforts in Bangka Regency, Indonesia. A qualitative case study approach was employed, involving in-depth interviews with 15 key informants representing government agencies, academia, civil society, media, and the private sector. Data were collected between February and April 2025 and analyzed thematically using the framework of collaborative governance developed by Ansell and Gash, complemented by a SOAR (Strengths, Opportunities, Aspirations, Results) analysis. Findings indicate that although a formal convergence structure exists through the Stunting Reduction Acceleration Team (TPPS), notable gaps persist in role clarity, coordination, and monitoring mechanisms. Strengths identified include strong political commitment, accredited health facilities, and supportive local regulations on sanitation and smoke-free areas. However, implementation varies across stakeholders, with unequal participation and limited outreach to remote areas. The SOAR analysis revealed key aspirations, including equitable premarital health services, behavioral change strategies, and improved performance monitoring. The study underscores the potential of collaborative governance to advance stunting prevention efforts, while emphasizing the need for improved institutional alignment, capacity building, and integrated monitoring systems. Strengthening stakeholder engagement and leveraging local aspirations into measurable actions are critical to achieving sustainable health outcomes. Keywords: Collaborative governance, Stunting, Ansell and Gash, SOAR, Indonesia